Public Perception of the Revitalization of Roro Dompak Port in Tanjungpinang City - Ananda, Riska; Lonika, Tri Asha; Putri, Rizqi Apriani (CV. Austronesia Akademika, 2025)
Port infrastructure plays a crucial role in supporting economic growth, connectivity, and public services, particularly in archipelagic regions such as Indonesia. Roro Dompak Port in Tanjungpinang City is a strategic transportation hub connecting the Riau Islands Province to surrounding areas, yet it has faced challenges in infrastructure quality, service efficiency, and user comfort. This study aims to analyze public perception of the port’s revitalization program and its impact on service quality and passenger satisfaction. A quantitative survey approach was applied, involving 518 purposively selected respondents, including passengers, vehicle owners, and logistics operators. Data were collected through a structured questionnaire covering service aspects such as cleanliness, security, facilities, officer responsiveness, ticketing, and departure flow, measured using the Community Satisfaction Index (CSI). The findings indicate that overall satisfaction falls within the “less good” category, with an average score of 2.95. While 66.7% of respondents rated waiting room cleanliness as “good” and improvements such as canopies and parking arrangements positively influenced comfort, other areas require enhancement. The revitalization has been well-received by the public, particularly in terms of new facilities and better passenger experience, but gaps remain in infrastructure capacity and operational performance. In conclusion, the study highlights the importance of aligning technical upgrades with community needs, enhancing service transparency, and fostering collaboration among stakeholders to ensure sustainable port development. The results provide empirical insights to guide strategic improvements that can strengthen Roro Dompak Port’s role in regional economic integration and maritime connectivity.